2015
DOI: 10.1002/jctb.4728
|View full text |Cite
|
Sign up to set email alerts
|

Vapour phase hydrogenolysis of glycerol to propanediols over Cu/SBA‐15 catalysts

Abstract: BACKGROUND: Biomass-derived glycerol is emerging as a renewable, cheap and versatile feedstock for the production of a variety of chemicals and fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 50 publications
3
15
0
6
Order By: Relevance
“…Most recently, studies on glycerol hydrogenolysis have been conducted by many researchers, with most of the studies focused on testing various catalysts and/or the effect of catalyst support materials . For example, Zhu et al reported that the Cu/SiO 2 catalyst developed from a pure‐phase copper phyllosilicate precursor was efficient and robust in glycerol hydrogenolysis to 1,2‐propanediol.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, studies on glycerol hydrogenolysis have been conducted by many researchers, with most of the studies focused on testing various catalysts and/or the effect of catalyst support materials . For example, Zhu et al reported that the Cu/SiO 2 catalyst developed from a pure‐phase copper phyllosilicate precursor was efficient and robust in glycerol hydrogenolysis to 1,2‐propanediol.…”
Section: Introductionmentioning
confidence: 99%
“…Selective oxidation of benzyl alcohol in organic solvents such as dioxane, DMF, acetonitrile, and THF were investigated by CuNi/TiO 2 , CuNi/MIL-101, and CuNi/C at 100 • C for 4 h under 5 bar, 3 bar, and 5 bar of O 2 . The best catalytic performance was observed in THF ( Table 2, entries 4-7, 13-16, and [22][23][24][25]. Moreover, in the optimization of the reaction temperature of the CuNi/MIL-101, CuNi/TiO 2 , and CuNi/C catalysts for the oxidation of benzyl alcohol, benzyl alcohol conversion continuously increased with increasing reaction temperature from 80 • C to 120 • C, along with a decreased benzaldehyde selectivity as oxidation is usually endothermic; thus, deep oxidation of benzaldehyde to benzoic acid easily occurred at high reaction temperatures ( [28][29][30].…”
Section: Benzyl Alcohol Oxidation Using Cu-ni Bimetallic Catalystsmentioning
confidence: 99%
“…Ammonia temperature programmed desorption (NH3-TPD) was used to measure the acidic properties of the MIL-101, TiO2, and C supports, and the results are shown in Figure 2. Three peaks were observed on the spectra of MIL-101 in the range of 40 °C-600 °C, whereas one broad peak was observed on the spectra of TiO2 and C. The low-temperature desorption peak centered at approximately 270 °C was attributed to adsorbed NH3 on Lewis acid sites, whereas the high-temperature desorption peak at approximately 340 °C was assigned to Brønsted acid sites [21][22][23][24][25]. TiO2 contained only Brønsted acid sites, C mainly possessed Lewis acid sites, and MIL-101 preliminarily included Lewis and Brønsted acid sites.…”
Section: Introductionmentioning
confidence: 99%
“…La mayor parte de los catalizadores soportados basados en Cu se han preparado mediante la técnica de impregnación a humedad incipiente, empleando Cu(NO3)2 como precursor [62,66,80,[168][169][170][171][172][173][174][175][176][177][178][179][180]. No obstante, esto, se han utilizado métodos de coprecipitación [66,[181][182][183], deposición-precipitación [184][185][186] e intercambio iónico [174,187].…”
Section: Cobreunclassified
“…Catalizadores de Cu/SBA-15 fueron evaluados y encontraron que para un contenido de Cu del 5 %p/p se obtuvo el máximo rendimiento a 1,2-PG. Los resultados también fueron atribuidos a la mayor dispersión de la fase activa, bajo la forma de partículas de óxido de cobre CuO que poseen menor tamaño que aquellas formadas a altos contenidos de Cu (20 %p/p) [178].…”
Section: Tabla 15-2 Hidrogenólisis 12-pg En Reactores Batch En Faseunclassified